Intellectual Property and Technology Transfer Department – 30 Years of History as an Academic Unit of the University of National and World Economy, Implementing Research and Training in The Field of Intellectual Property (UNWE Yearbook, 2023)
The subject of this study is to present the 30-year history of the Intellectual Property and Technology Transfer Department in terms of educational services provided and research results.The aim of the study is to present information about the positions won in the market of educational services for over 30 years and the efforts made to maintain the good image of the Intellectual Property and Technology Transfer Department and the Institute of Intellectual Property and Technology Transfer nationally and internationally, and thus of the University of National and World Economy, to which structure these two units belong.The approaches and tools applied in the study are a historical, complex, and systematic approach, methods of generalizations, selection, and analysis.